Understanding statebuilding traditional governance and the modern state in Somaliland - Richards, Rebecca (Routledge, 2016)
Much analysis of state building focusses on dissecting specific projects and attempting to identify what has gone 'wrong' in states such as Afghanistan and Iraq. What draws less attention is what has gone 'right' in non-interventionist statebuilding projects within 'unrecognised' states. By examining this model in more depth a more successful model of statebuilding emerges in which the end goal of modern democracy and good governance are more likely to be realized. Indeed 'states-within-states' such as Somaliland where external intervention in the statebuilding process is largely absent can provide vital new lessons. Somaliland is a functioning democratic political entity in northwestern Somalia which declared its independence from the troubled south in 1991 and then embarked on an ambitious project to create a democratic government and successful state in the post-conflict environment. The leaders and the people of Somaliland have since succeeded not only in maintaining peace and stability, but also in building the institutions of government and the foundations for democracy that have led to a succession of elections, peaceful transfers of power and a consolidation of democratization. The resulting state of Somaliland is widely hailed as a beacon of success within a politically turbulent region and provides a useful framework for successful statebuilding projects throughout the world.